Socialization on the Use of Medicinal Plants in Kuripan Village, Kuripan District, West Lombok Regency - Dwi Melinda Sari; Eka Wuri Handayani; Chondrosuro Miyarso (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Traditional medicine is ingredients or ingredients derived from plants, animals, minerals,preparations of extracts (galenic), or mixtures of these materials, which have been used forgenerations for treatment based on experience. The use of traditional medicine in Indonesia has longbeen known. However, knowledge about what plants can be used, the dose, side effects of drugs thatmay appear, and how to process medicinal plants that will be used correctly are not widely known bythe public. The wrong dose and the wrong way of processing will result in the therapeutic objectiveswith the plants used being unable to be achieved. The counseling activity was carried out in Kuripanvillage, Kuripan sub-district, West Lombok district, which aims to provide information on how to usetraditional medicinal plants commonly consumed by the community. The method used is Focus GroupDiscussing (FGD) with media power pints and leaflets. The results of the counseling showed that thecommunity had increased knowledge as evidenced by the increase in the posttest score with an averagevalue of 84. After this service was carried out, it could be seen that the community had known andapplied good traditional medicine processing methods. It is hoped that with this treatment goals can beachieved maximally and with minimal side effects so that it has an impact on improving the quality ofpublic health.